Dilute lidocaine suppresses ectopic neuropathic discharge in dorsal root ganglia without blocking axonal propagation: a new approach to selective pain control. Issue 7 (July 2018) - Koplovitch, Pini; Devor, Marshall
Abstract : Abstract: Ectopic impulse discharge (ectopia) generated in the soma of afferent neurons in dorsal root ganglia (DRG) after nerve injury is believed to be a major contributor to neuropathic pain. The DRG is thus a prime interventional target. The process of electrogenesis (impulse generation) in the DRG is far more sensitive to systemically administered Na + channel blockers than the process of impulse propagation along sensory axons. It should therefore be possible to selectively suppress DRG ectopia with local application of membrane-stabilizing agents without blocking normal impulse traffic. Results from in vivo electrophysiological recordings in rats showed that epidural application of lidocaine to the DRG surface within the intervertebral foramen at 0.02% or 0.2% substantially suppresses electrogenesis in the DRG with only a modest blocking effect on impulse propagation through the foramen. Topically applied opiates and gamma aminobutyric acid, by contrast, blocked neither ongoing discharge nor spike through-conduction. This suggests that sustained intraforaminal delivery of dilute lidocaine, and by extension other membrane-stabilizing agents, is a potential new strategy for the control of chronic painful conditions in which ectopia in sensory ganglia is implicated as a key pain driver. Such conditions include postherpetic neuralgia, trigeminal neuralgia, phantom limb pain, complex regional pain syndrome, and radicular low back pain. Abstract : Dilute lidocaine applied intraforaminally might control pain in major clinical neuropathic pain conditions, as suggested by electrophysiological recordings from dorsal root ganglia in an animal neuropathy model.